2008
DOI: 10.1371/annotation/a6c35a12-e8eb-43a0-9d00-5078fa6da1bb
|View full text |Cite
|
Sign up to set email alerts
|

Correction: The Zinc Transporter SLC39A13/ZIP13 Is Required for Connective Tissue Development; Its Involvement in BMP/TGF-β Signaling Pathways

Abstract: Background: Zinc (Zn) is an essential trace element and it is abundant in connective tissues, however biological roles of Zn and its transporters in those tissues and cells remain unknown.Methodology/Principal Findings: Here we report that mice deficient in Zn transporter Slc39a13/Zip13 show changes in bone, teeth and connective tissue reminiscent of the clinical spectrum of human Ehlers-Danlos syndrome (EDS). The Slc39a13 knockout (Slc39a13-KO) mice show defects in the maturation of osteoblasts, chondrocytes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 51 publications
4
31
0
Order By: Relevance
“…Another finding related to osteogenesis imperfecta that may be associated with improper zinc management is the observation that patients with a novel type of Ehlers‐Danlos/osteogenesis imperfecta syndrome, who exhibit features characteristic of both Ehlers‐Danlos syndrome and osteogenesis imperfecta, possess a loss‐of‐function mutation in the zinc transporter ZIP13 (44). Indeed, Zip13 knockout mice show a phenotype that shares many similarities with these patients, and osteoblasts isolated from these mice show disorganized differentiation and impaired matrix‐producing functions (45), suggesting that zinc management must be tightly controlled for proper osteoblast function.…”
Section: Discussionmentioning
confidence: 99%
“…Another finding related to osteogenesis imperfecta that may be associated with improper zinc management is the observation that patients with a novel type of Ehlers‐Danlos/osteogenesis imperfecta syndrome, who exhibit features characteristic of both Ehlers‐Danlos syndrome and osteogenesis imperfecta, possess a loss‐of‐function mutation in the zinc transporter ZIP13 (44). Indeed, Zip13 knockout mice show a phenotype that shares many similarities with these patients, and osteoblasts isolated from these mice show disorganized differentiation and impaired matrix‐producing functions (45), suggesting that zinc management must be tightly controlled for proper osteoblast function.…”
Section: Discussionmentioning
confidence: 99%
“…The latter finding is typically observed in collagen lysyl hydroxylase deficiency (EDS type VI-A), but in that condition, there is severe muscular hypotonia from birth, progressive kyphoscoliosis, and normal height (apart from kyphoscoliosis). Additionally, there were no pathogenic mutations in PLOD1; instead, the patients reported by Giunta et al (2008) were homozygous for an in-frame 9-bp deletion in SLC39A13, c.483_491del (p.F162_164del), while those reported by Fukada et al (2008) were homozygous for the SLC39A13 variant c.221G>A (p.G74D). The novel condition was given the name of "spondylo-cheiro-dysplastic EDS" for the distinguishing features of the hand and the platyspondyly [4,5].…”
Section: Introductionmentioning
confidence: 98%
“…A connective tissue disorder associated with recessive biallelic variants in SLC39A13, and a mouse knock-out model for the same gene, were described in 2008 by two separate but collaborating groups [4,5]. The features noted in these eight patients were postnatal-onset short stature, protuberant eyes with bluish sclerae and down-slanting palpebral fissures, thin and moderately hyperelastic skin with bruisability, and hands with finely wrinkled palms, tapering fingers, thenar atrophy, and moderate hypermobility of the small joints.…”
Section: Introductionmentioning
confidence: 99%
“…A secondary messenger involved in many signaling pathways [24,27,29,30,31,32], zinc plays a critical role in cell survival and migration [24,31,32,33]. Zinc homeostasis associated with bone growth is facilitated by transporter proteins from the Slc39/Zip and Slc30/ZnT families [34,35,36]. Of particular importance are Zip13 and Zip14, which are involved in intracellular zinc distribution and regulation of mammalian systemic growth via the BMP/TGF-β and G-protein coupled receptor (GPCR)-mediated signaling pathways [34,35], as well as Znt5, which is critical for osteoblast maturation in vitro and maintenance of bone density in vivo [36].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc homeostasis associated with bone growth is facilitated by transporter proteins from the Slc39/Zip and Slc30/ZnT families [34,35,36]. Of particular importance are Zip13 and Zip14, which are involved in intracellular zinc distribution and regulation of mammalian systemic growth via the BMP/TGF-β and G-protein coupled receptor (GPCR)-mediated signaling pathways [34,35], as well as Znt5, which is critical for osteoblast maturation in vitro and maintenance of bone density in vivo [36]. Recent studies have shown that zinc is involved in the late-stage expression of RUNX2, a gene that has been suggested to be essential for recruiting migratory osteoblasts during bone mineralization [37,38].…”
Section: Introductionmentioning
confidence: 99%